Genomic Comparison of Eight Closed Genomes of Multidrug-Resistant Salmonella enterica Strains Isolated From Broiler Farms and Processing Plants in Trinidad and Tobago - Maguire, Meghan; Khan, Anisa S.; Adesiyun, Abiodun A.; Georges, Karla; Gonzalez-Escalona, Narjol (Frontiers in Microbiology, 2022)
Salmonella enterica is an important foodborne pathogen worldwide. We used long and short read sequencing to close genomes of eight multidrug resistant (MDR) Salmonella enterica strains, belonging to serovars Infantis (2), Albany, Oranienburg, I 4,[5],12:i:-, Javiana, Schwarzengrund, and Kentucky from broiler chicken farms and processing plants in Trinidad and Tobago. They also belonged to seven different sequence types (STs- 32, 292, 1510, 19, 24, 152, and 96). Seven of the strains demonstrated multi-drug resistance with the presence of at least three AMR genes. Three isolates contained the quinolone resistance gene qnrB19 in plasmids (CFSAN103840, CFSAN103854, and CFSAN103872). The extended spectrum -lactamase genes blaCTX-M-65 (CFSAN103796) and blaTEM-1 (CFSAN103852) were detected in this study. The genomes closed in this study will be useful for future source tracking and outbreak investigations in Trinidad and Tobago and worldwide. dy will be useful for future source tracking and outbreak investigations in Trinidad and Tobago and worldwide.